2007
DOI: 10.1021/ac0713961
|View full text |Cite
|
Sign up to set email alerts
|

Heteronuclear 1H−31P Statistical Total Correlation NMR Spectroscopy of Intact Liver for Metabolic Biomarker Assignment:  Application to Galactosamine-Induced Hepatotoxicity

Abstract: As part of our ongoing development of methods for enhanced biomarker information recovery from spectroscopic data we present the first example of a new hetero-nuclear statistical total correlation spectroscopy (HET-STOCSY) approach applied to intact tissue samples collected as part of a toxicological study. One-dimensional 1H and 31P-{1H} magic angle spinning (MAS) NMR spectra of intact liver samples after galactosamine (galN) treatment to rats and after cotreatment of galN plus uridine were collected at 275 K… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
166
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(173 citation statements)
references
References 53 publications
5
166
2
Order By: Relevance
“…There are now numerous applications of STOCSY and closely related covariance techniques for enhanced information recovery from low dimensional NMR data sets on multiple and single samples [3][4][5][6][7][8][9][10][11][12][13] . The STOCSY approach has been applied to the structural assignment problem in a variety of NMR metabolic profiling contexts, such as deconvolution of overlapped chromatographic peaks in LC-NMR 7 , delineation of drug metabolism in molecular epidemiology studies 5 and separation of different molecular signatures in diffusion edited spectroscopy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…There are now numerous applications of STOCSY and closely related covariance techniques for enhanced information recovery from low dimensional NMR data sets on multiple and single samples [3][4][5][6][7][8][9][10][11][12][13] . The STOCSY approach has been applied to the structural assignment problem in a variety of NMR metabolic profiling contexts, such as deconvolution of overlapped chromatographic peaks in LC-NMR 7 , delineation of drug metabolism in molecular epidemiology studies 5 and separation of different molecular signatures in diffusion edited spectroscopy 6 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in this study, the acquisition of 2D 1 H-1 H TOCSY and 1 H-31 P HSQC correlation spectra has enabled the identification of the spin systems for the main metabolites in 31 P spectra and has confirmed the assignments with the homonuclear and the heteronuclear correlations. Previously it had been demonstrated that the metabolic information could be improved by the combination of 1D 1 H and 31 P spectra, constructing afterwards a kind of virtual 2D heteronuclear correlation [18,39]. This 1D heteronuclear strategy has been applied in human to the study of gut biopsies to detect different tissue microenvironments [18] and in rat liver for the detection of druginduced hepatotoxicity [39].…”
Section: Discussionmentioning
confidence: 99%
“…Previously it had been demonstrated that the metabolic information could be improved by the combination of 1D 1 H and 31 P spectra, constructing afterwards a kind of virtual 2D heteronuclear correlation [18,39]. This 1D heteronuclear strategy has been applied in human to the study of gut biopsies to detect different tissue microenvironments [18] and in rat liver for the detection of druginduced hepatotoxicity [39]. The study here presented, has shown the feasibility of 1 H-31 P HSQC spectra acquisition on human brain tumour tissue with signal to noise ratio adequate to observe the signals from the main metabolites identified in the 31 Additionally, a remarkable advantage of the 31 P spectra is that allow an estimation of the pH inside the tissue samples, that relies in the change in the chemical shift of some phosphorylated metabolites present in the living tissues.…”
Section: Discussionmentioning
confidence: 99%
“…H NMR spectra) to generate a pseudo-two-dimensional NMR spectrum that displays the correlation among the intensities of the various peaks across the whole sample. In heteronuclear (HET)-STOCSY [9], calculation of the covariance between the 31 P-NMR and 1 H NMR signals of phosphorus containing metabolites allows their molecular connectivities to be established. The construction of virtual two-dimensional HET correlation spectra that connect all protons on the molecule to the heteroatom was achieved.…”
Section: Introductionmentioning
confidence: 99%